Successful non-operative management of spontaneous type II gallbladder perforation in a patient with Alzheimer's disease. (23rd May 2014) - Alessiani, Mario; Peloso, Andrea; Tramelli, Paola; Magnani, Enzo
Abstract : A 77-year-old man with Alzheimer's disease was admitted to a rural hospital in June 2012 and an acute cholecistytis was first diagnosed. Surgery was not considered as a possible option due to the critical condition of the patient and his severe comorbidities. After 2 days of broad-spectrum antibiotics, the patient worsened and developed severe sepsis. A gallbladder perforation with intrahepatic abscess formation was diagnosed on ultrasonography (US) and abdominal CT scan. The patient underwent percutaneous US-guided gallbladder drainage with resolution of the sepsis and rapid clinical improvement. After 1 month, the drainage was removed and the patient was discharged. He survived in good condition for 18 months and he passed away from pneumonitis in December 2013. This case shows that in a case of acute cholecystitis with gallbladder perforation, percutaneous gallbladder drainage can be a lifesaving procedure in elderly patients with severe comorbidities (including Alzheimer's disease) who are not candidates for elective surgery.